The moderating influence of organizational culture and organizational capacity on the association between corporate governance and performance of Malaysian listed companies - Ifa Rizad Mustafa (Kulliyyah of Economics and Management Sciences, International Islamic University Malaysia, 2013)
The aim of this study is to assess the influence of corporate governance, organizational culture and capacity on the performance of companies listed on Bursa Malaysia. The introduction of the MCCG in 2000, which stresses accountability and transparency, is expected to provide evidence that those companies that complied with the recommendations result in better performance. Additionally, the current study is motivated to examine the moderating effect of organizational culture and capacity on the association between corporate governance and performance since no prior studies have reported on the work albeit they examined the influence of these variables independently. The study focuses on achieving three objectives: 1) examining the influence of corporate governance on performance; 2) assessing the moderating effect of organizational culture, and; 3) determining the effect of organizational capacity as moderator between corporate governance and performance. This study employs corporate annual reports and questionnaire survey in data collection. This study contributes to the theory by employing the organizational culture theory and resourcebased view of the firm perspective in developing the hypotheses. The current study further contributes to the methodology by demonstrating the interaction terms in assessing the effect of moderators on performance. Practically, the finding on leverage contributes by indicating that Malaysia will attract more foreign investment with its good banking system. A further contribution to the practice is reported as top management appears to promote flexibility culture in a company. Another practical implication is that a company needs to have adequate infrastructure and utilize it appropriately because its interaction with corporate governance is proven to have an influence on company performance. Taken together, the findings of this study recognize the importance of leverage among Malaysian companies, acknowledge that different types of culture are significant in certain scenarios or environments and verify that infrastructure emerges as an important element to the study of corporate governance.